Aprendizagem Cooperativa: construção e reconstrução da identidade docente a partir da Teoria Dialógica do Discurso - Lima, Alverbênia Maria Alves de (2021)
This paper concerns the spread of the Cooperative Learning methodological approach in the state of Ceará and how professors have been prepared with such approach in the Federal University of Ceará (UFC) thanks to the School Cooperation Promotion Program (PRECE). Since the graduate’s initial steps towards the teaching occupation are essential to develop this “teacher identity”, the purpose of this thesis is to assess how those professors, still initiating in said occupation, embrace “recreating” their teacher identity in view of the mentioned methodology. As said graduates were asked to write about their experience under this approach, this paper now assesses those writings based on the Dialogical Theory of the Discourse. The main theoretical bases provided herein are the Cooperative Learning (JOHNSON; JOHNSON; HOLUBEC, 1999; OVEJERO, 1990; LOPES; SILVA, 2009; CARVALHO; ANDRADE NETO, 2019), the Dialogical Theory of the Discourse (BAKHTIN, 1997, 2011, 2015, 2018; VOLÓCHINOV, 2018; BARROS, 2003; AMORIM, 2006), and the Teacher Identity (ABRIC, 2011; SEIDMANN, 2015; MARKOVÁ, 1996, 2006; CLOT, 2010, 2016). The methodology applied to this paper is a qualitative one. The data collection was undertaken through a documentary research of the reports written by the holders of Licentiate degrees from UFC and former holders of scholarships from the Letras Solidárias Project, all of them telling their experiences – to clarify, the Letras Solidárias Project is related to PRECE. The corpus consists of said reports written by five holders of Licentiate degrees in Language Arts who were involved with the Letras Solidárias Project in 2018 and 2019, acting as professors there and in state schools. The main result extracted from this study is that affective relationships arose among those involved in the study and other groups and that those affections may diminish or improve the capacity of acting to those prospective professors. Moreover, despite the impossibility to create a discourse that encompasses everything, we were able to understand some of the “represented” identities, such as the one concerning a professor who values the life story of another, engages in practicing their social skills, has a plan of action, assesses their actions and those of their peers, develops bonds with the students, and values cooperation and solidarity. Such revealed identities make sense in view of the expected impact from the Cooperative Learning methodology in developing the identity of the prospective teachers. Therefore, the scholarship holders, with their discourse set in a given time and space, through reports on their experiences present their biases and identities, which are neither fixed nor unquestionable as they are developed in the relations with the Other.